(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Interactive forms and methods in teaching foreign languages have become increasingly prevalent in language education due to their effectiveness in engaging learners and promoting active participation. This article explores the various interactive forms and methods used in language teaching, including communicative activities, task-based learning, project-based learning, and technology-enhanced approaches. It examines the benefits of interactive language instruction, discusses practical strategies for implementation, and explores the implications for language educators and learners. By harnessing the power of interactive teaching methods, educators can create dynamic and immersive language learning experiences that foster language proficiency and cultural competence.